A Novel Polymeric Nanohybrid Antimicrobial Engineered by Antimicrobial Peptide MccJ25 and Chitosan Nanoparticles Exerts Strong Antibacterial and Anti-Inflammatory Activities - Haitao, Yu; Yifan, Chen; Mingchao, Sun; Shuaijuan, Han (Frontiers in Immunology, 2022)
Infection caused by antibiotic-resistant microorganisms (ARMs) has been declared a global threat to public health. Polymeric nanoparticles (PNPs) formed by antimicrobial peptides (AMPs) and synthetic PNPs against ARM infections are emerging. PNPs are also considered to be a promising natural biological preservative that prevents microbial spoilage through food processing and preservation. We engineered CNMs, a novel nanocomposite antibacterial agent based on chitosan nanoparticles and AMP microcin J25. In this study, we aimed to evaluate the comprehensive antimicrobial activity, potential antimicrobial mechanism, and anti-inflammatory activity of CNMs. We demonstrated that CNMs harbor excellent bactericidal activity against clinical foodborne pathogens and ARMs. CNMs caused fast mortality against different growth phases of tetracycline (Tet)-resistant enterotoxigenic E. coli (ETEC) and significantly killed Tet-resistant ETEC in food biological environments. Mechanistically, CNMs have the ability to bind lipopolysaccharides (LPS), neutralize endotoxin, and promote diaphragm permeability by damaging the cell membrane. CNMs did not cause mouse RAW264.7 cell cytotoxicity. Notably, CNMs significantly reduced the cytotoxicity of RAW264.7 macrophages induced by LPS. The LPS-induced inflammatory response was significantly ameliorated by CNMs by reducing the levels of nitric oxide and proinflammatory cytokines, including tumor necrosis factor α, interleukin (IL)-6, IL-8, IL-1β, Toll-like receptor 4 and nuclear factor κB (NF-κB), in LPS-challenged RAW264.7 macrophages. CNMs downregulated the NF-κB and mitogen-activated protein kinase signaling pathways, thereby inhibiting inflammatory responses upon LPS stimulation. Taken together, CNMs could be applied as effective antimicrobial/anti-inflammatory agents with lower cytotoxicity in food, medicine, and agriculture to prevent bacterial contamination and infection, respectively.